2019
DOI: 10.2147/dddt.s202730
|View full text |Cite
|
Sign up to set email alerts
|

<p>Pharmacokinetic comparison of a fixed-dose combination versus concomitant administration of amlodipine, olmesartan, and rosuvastatin in healthy adult subjects</p>

Abstract: Objective: The aim of this study was to compare the pharmacokinetic (PK) and safety profiles of a fixed dose combination (FDC) formulation and co-administration of amlodipine, olmesartan, and rosuvastatin. Materials and methods: This study was an open-label, randomized, cross-over design conducted in healthy male volunteers. All subjects received either a single FDC tablet containing amlodipine 10 mg/olmesartan 40 mg/rosuvastatin 20 mg, or were co-administered an FDC tablet c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The number of study population which was able to meet the bioequivalence criteria with a significance level of 0.05 and 90% power was statistically calculated based on the previous study in which the highest value of intra-individual CV of PK parameter among the three active drugs and one metabolite was for the C max of losartan, which was about 36.5%. 16 Of the 56 subjects who completed this study, the highest value of the intra-individual CV was 30.80% (C max of losartan). The number of participants enrolled in the study validates the bioequivalence between the two treatments.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The number of study population which was able to meet the bioequivalence criteria with a significance level of 0.05 and 90% power was statistically calculated based on the previous study in which the highest value of intra-individual CV of PK parameter among the three active drugs and one metabolite was for the C max of losartan, which was about 36.5%. 16 Of the 56 subjects who completed this study, the highest value of the intra-individual CV was 30.80% (C max of losartan). The number of participants enrolled in the study validates the bioequivalence between the two treatments.…”
Section: Discussionmentioning
confidence: 89%
“…Similar to other comparative studies of FDC formulations of CCBs, ARBs, and statins, GMRs of all primary pharmacokinetic parameters were close to 1. 15,16 Approximately 14% of EXP3174, an active metabolite of losartan with a half-life of around 6 to 9 h, is formed by CYP2C9 and CYP3A4, and it is 10-to 40-fold more potent than losartan. 17 In addition to the active drugs, the PK profile of EXP3174 was analyzed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this combination, we added rosuvastatin as a separate pill. This triple combination as SPC provided good safety and efficacy data and pharmacokinetic profile [29].…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have shown no pharmacokinetic (PK) interaction between olmesartan and amlodipine. In the fixed‐dose combination, olmesartan and amlodipine have synergistic antihypertensive effects, which can be used for preliminary treatment of hypertension 8,12,13 . The brand‐named preparation made by Daiichi Sankyo Europe GmbH was widely used in 30 countries around the world.…”
Section: Methodsmentioning
confidence: 99%